Females and Precarious Board Positions: Further Evidence of the Glass Cliff. (5th December 2013) - Mulcahy, Mark; Linehan, Carol
<x xml:space="preserve">Abstract</x> The 'glass cliff' posits that when women achieve high profile roles, these are at firms in precarious positions. Previous research analysed appointments (male/female), estimated the precariousness of firms involved and drew inferences about the glass cliff. This study is different as it directly tests the relationship between a precarious situation and changes in board gender diversity. The sample is companies listed on the UK stock exchange reporting an initial loss in the years 2004–2006. A matched control sample is used in a difference‐in‐differences analysis to avoid inadvertently attributing improvements arising from societal/regulatory changes in gender diversity to the loss event. Findings suggest that when the loss is 'big' there is a difference in the increase in gender diversity versus both the control and the 'small' loss subsamples, i.e. compelling evidence of the glass cliff. In the context of ongoing political and social debates about women on boards our work (i) identifies continuing structural barriers for women ascending to board level in that women are more likely to be over‐represented on boards of companies that are more precarious and (ii) sounds a note of caution about celebrating increased gender diversity on boards without considering the precariousness of the company involved.